Morpho-functional parameters of neurons in the sensorimotor cortex and neuroapoptosis under conditions of an induced experimental allergic encephalomyelitis in rats and a course of intranasal gel administration containing n-phenylacetyl-l-prolylglycine (Noopept) - Burlaka, B. S.; Bielenichev, I. F.; Nosach, S. G.; Nefedov, А. А.; Бурлака, Богдан Сергійович; Бєленічев, Ігор Федорович; Носач, Світлана Григорівна (My University, 2021)
The aim of the research is to evaluate a neuroprotective effect of the nasal dosage form containing Noopept (n-phenylacetyl-l-prolylglycine ethyl ester) by the degree of influence on morphofunctional parameters of neurons in the sensorimotor cortex of animals with experimental allergic encephalomyelitis. Methods. The experiments were conducted on 260 outbred albino rats weighing 190- 220 g which were obtained from the nursery of the State Institution «Institute of Pharmacology and Toxicology of the Academy of Medical Sciences of Ukraine». The quarantine (acclimatization period) for all animals lasted 14 days. An animal model of 192 experimental allergic encephalomyelitis (EAE) which has clinical manifestations and pathogenic mechanisms similar to multiple sclerosis was used for the study. There were five groups of animals in the experiment: 1) the intact group (10 rats); 2) the control group – nontreated subjects with EAE which received saline solution (20 rats); 3) the animals with EAE which received basic treatment – 3,4 mg / kg of Methylprednisolone (MP) intraperitoneally, administered slowly in saline solution with a volume of not more than 1/10 of the blood volume of a rat (20 rats); 4) the animals with EAE which received MP and a nasal gel containing n-phenylacetyl-l-prolylglycine at a dose of 10 mg / kg (20 rats); 5) the animals with EAE which received MP and Citicolinum (Ceraxon, «Ferrer Internacional S.A.», Spain) series D003U1, 500 mg / kg, intragastrically (20 rats). Morphometric studies were carried out with the help of Axioskop microscope (Ziess, Germany), a magnification of x40. The image of neurons in the area of the CA-1 zone of the hippocampus, obtained from the microscope using a highly sensitive video camera COHU-4922 (COCHU Inc., USA). Results. It has been shown that the combination therapy with Methylprednisolone and an intranasal gel containing n-phenylacetyl-l-prolylglycine intensified neuroprotectivity in the animals with EAE. In particular, a neuronal density in rats with the experimental pathology, which received a combination of Methylprednisolone and a gel containing n-phenylacetyl-lprolylglycine, increased by 14,7 (р <0,05) and their area equaled in values with animals from the intact group; at the same time, the amount of RNA increased by 9,2%. In addition, in conditions of this experiment n-phenylacetyl-l-prolylglycine decreased density of apoptotic and destructive cells by 32,4% (р <0,05) in relation to the control and the MP groups, and the amount of apoptotic neurons – by 44,6% (р <0,05). Judging by effect on the neuronal density and the density of apoptotic and destructively altered neurons in the sensorimotor cortex of outbred albino rats with EAE, a combination of Methylprednisolone and a gel containing nphenylacetyl-l-prolylglycine reliably exceeds the combined therapy of Methylprednisolone and Citicolinum and the MP monotherapy. A higher, according to some indicators, neuroprotective, nootropic, anxiolytic activity of a gel containing n-phenylacetyl-lprolylglycine is due to its intranasal route of administration. Conclusions: For the first time, we have obtained reliable data on the neuroprotective effect of the new dosage form containing n-phenylacetyl-l-prolylglycine (Noopept) – an intranasal gel – under conditions of an induced experimental multiple sclerosis. It has been shown that a course of intranasal administration of a gel containing n-phenylacetyl-lprolylglycine (Noopept) at a dose of 10 mg / kg in combination with Methylprednisolone leads to a decrease in the death of neurons in the sensorimotor cortex of rats with EAE and an 193 increase in the amount of RNA in them. It has been shown that a course of intranasal administration of a gel containing n-phenylacetyl-l-prolylglycine (Noopept) at a dose of 10 mg / kg in combination with Methylprednisolone leads to neuroapoptosis inhibition – a decrease in the density of apoptotic and destructively altered neurons in the sensorimotor cortex of outbred albino rats with EAE. It has been found that judging by effect on the neuronal density and the density of apoptotic and destructively altered neurons in the sensorimotor cortex of the outbred albino rats with EAE, a combination of Methylprednisolone and a gel containing n-phenylacetyl-l-prolylglycine reliably exceeds the combined therapy of Methylprednisolone and Citicolinum and the MP monotherapy.
Keywords: n-phenylacetyl-l-prolylglycine; neuroapoptosis; intranasal gel